APPLICATION OF THE TWO STAY TWO STRAY (TSTS) LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN SOCIAL STUDY CLASS V STATE 32 PRIMARY SCHOOL BANDA ACEH - Hayati, Safrina; Mislinawati, Mislinawati; Ahadin, Ahadin (Elementary Education Research, 2024)
This research aims to describe student activities, teacher activities and to determine student learning outcomes through the application of the Two Stay Two Stray learning model in social studies lessons in class V of SD Negeri 32 Banda Aceh. The subjects in this research were 24 students, consisting of 13 women and 11 men. The data collection techniques used are observation and tests. Data analysis uses qualitative descriptive analysis using the percentage formula. The results of the data analysis carried out showed that there was an increase in teacher activity in managing learning in cycle I, getting an average score of 3 with good criteria, cycle II got an average score of 3.5 with very good criteria. Student activity in learning showed an increase in cycle I with an average score of 52.62 with sufficient criteria, in cycle II the average score was 83.43 with very good criteria. Student learning outcomes show an increase, this is shown by the average value of test results for cycle I of 65 and cycle II of 84.58. This increase has reached the complete indicator. From the results of data analysis, it was concluded that the application of the Two Stay Two Stray (TSTS) learning model in social studies lessons could improve the learning outcomes of class V students at SD Negeri 32 Banda Aceh.